Silver Nanoparticle Biosynthesis using Distimake vitifolius Extract for Enhancement of Antibacterial and Antioxidant Activity - Tahya, Candra Yulius; Karnelasatri, Karnelasatri; Irawati, Wahyu; Munthe, Sri Wahyu Ningsih (Universitas Jenderal Soedirman, 2024)
ABSTRACT. The biological method for silver nanoparticle synthesis emphasizes green synthesis, which is faster, environmentally safer, facile, energy-efficient, and cost-effective. It provides good alternatives to physical and chemical methods. In this research, we have synthesized silver nanoparticles using D. vitifolius ethanolic extract. The 38 natural compounds of flavonoid, phenolic or polyphenol compositions have been determined by LC-MS/MS-QTOF which is carried out using UNIFI software equipped with a mass spectrum library of active substances from natural ingredients from the Waters database. Silver nanoparticle (Dv-AgNP) was characterized by using TEM and SEM where the average diameter of nanoparticle was seen <100 nm and confirmed by PSA analysis that the Z-average is 62.73 ± 0.71 nm. EDS spectrum confirmed the silver element as a major element of the particles. PI value of Dv-AgNP is 0.557, while the zeta potential is -17.37 ± 1.53 mV. Dv-AgNP can inhibit the growth of P. aeruginosa (amoxicillin resistant) with an inhibition zone of 15.83 ± 2.36 mm, and K. pneumoniae with an inhibition zone is 10.03 ± 0.55 mm. These are moderate inhibitory activities. The antioxidant result of the Dv-AgNP suspension solution shows that the IC50 is 0.58 mM. The IC50 of the crude extract is 752 ppm and is categorized as very weak antioxidant activity. Keywords: Antibacterial; D. vitifolius; silver nanoparticle.